(untitled) (Medico Legal Update, 2021)
Background: Analyzing and identifying evidences found at crime scene plays a crucial role in apprehending the offenders and putting them behind bars. Stature Estimation has a significant importance when it comes to narrowing down the list of suspects. At various instances footprints are left behind at the crime scenes as vital evidence and can be utilised for generating the stature of the individual/s connected with the crime scene. Method: The present study focuses on female population belonging to Rajasthan. Major objective is to determine relation between foot dimensions and stature (n=111). Foot dimensions, mainly foot length and breadth were calculated using standard measurements method. The samples were statistically analyzed; regression equations were generated for length and width of left and right foot. Conclusion: The predicted R-squared values showed quite significant value of left foot being (0.09) and right foot being (0.04). SEE was calibrated through the regression equations. Width of both the left and right foot were found to be more significant measurements for estimating stature in Rajasthan Population.